A modified lithium cobalt oxide positive electrode material and its preparation method and application

By forming an alumina cladding layer on the surface of the lithium cobalt oxide positive electrode material and converting it into a LATP layer, the problem of poor cyclability of the lithium cobalt oxide positive electrode material at high voltage is solved, and efficient lithium ion transmission and stable capacity maintenance are achieved.

CN118811866BActive Publication Date: 2025-02-07SHANDONG CHUANGLU ADVANCED BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411295746.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide positive electrode materials have poor cycling properties at high voltages, resulting in rapid capacity decay and difficulty in transfer of lithium ions, and the reaction of surface doped element Al with the electrolyte leads to instability in the interface.

Method used

By mixing the lithium cobalt oxide positive electrode material with aluminum triethanol and calcining, an alumina cladding layer is formed, and converted into a LATP layer during the subsequent coating process, forming a "double-coated" modified lithium cobalt oxide positive electrode material.

Benefits of technology

The stable structure of lithium cobalt oxide positive electrode material is realized, the circulation performance and capacity retention rate are improved, and the interface side reactions and loss of Al elements are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118811866B_ABST
    Figure CN118811866B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and specifically relates to a modified lithium cobalt oxide positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing cobalt oxide and lithium salt according to a molar ratio of Co in cobalt oxide: Li in lithium salt of 1:1.05 to obtain a mixture; (2) calcining the mixture to obtain a lithium cobalt oxide positive electrode material; (3) mixing the lithium cobalt oxide positive electrode material with aluminum triethanolate according to a molar ratio of Co in the lithium cobalt oxide positive electrode material: Al in aluminum triethanolate of 1:(γ×δ), and calcining to obtain lithium cobalt oxide coated with aluminum oxide; (4) mixing the lithium cobalt oxide coated with aluminum oxide with a lithium source, a titanium source and a phosphorus source according to a molar ratio of Al in lithium cobalt oxide: Li in lithium source: Ti in titanium source: P in phosphorus source of δ:(1+δ):(2‑δ):3, and calcining to obtain a modified lithium cobalt oxide positive electrode material. The modified lithium cobalt oxide positive electrode material prepared by the present invention significantly improves the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a modified lithium cobalt oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium cobalt oxide (LiCoO2) cathode materials are widely used in 3C electronic products due to their high compaction density. The theoretical capacity of LiCoO2 cathode materials is 274mAh / g, while the capacity of the currently widely used LiCoO2 cathode materials is only 140mAh / g, which means that only half of the Li + Although increasing the charging voltage can increase the specific capacity of the battery, it will also cause a sharp decline in capacity, resulting in extremely poor cycle stability, which is also the main bottleneck restricting the application of high-voltage, high-specific-energy lithium cobalt oxide positive electrode materials.

[0003] Studies have shown that the reason for the poor cyclability of high-voltage lithium cobalt oxide positive electrode materials is the unstable surface interface structure under high voltage. Under high voltage, as the charge and discharge cycle proceeds, the surface interface of the lithium cobalt oxide particles will gradually degenerate from a layered structure to a spinel structure, accompanied by the escape of lattice oxygen, causing rapid capacity decay, lithium ion transmission difficulties and other problems. Publication No. CN111987297A discloses a lithium-rich manganese-based positive electrode material and preparation coated with lithium titanium aluminum phosphate on the surface, the positive electrode material includes a lithium-rich manganese-based positive electrode material and a coating layer of lithium titanium aluminum phosphate wrapped outside the lithium-rich manganese-based positive electrode material, and the surface of the lithium-rich manganese-based positive electrode material is doped with Al. The effect of effectively stabilizing the lattice oxygen to prevent phase change and improve the cycle performance is achieved. However, this method still has the following defects: the surface doping element Al will react with LiPF6 in the electrolyte during the cycle, resulting in instability of the interface between the positive electrode and the electrolyte and the loss of Al elements in the bulk phase.

[0004] Therefore, there is an urgent need to develop a surface coating method for lithium cobalt oxide positive electrode materials that has a uniform surface coating effect, a coating layer with stable physical and chemical properties and can enhance ion transport. Summary of the invention

[0005] In order to solve the defects of the above-mentioned prior art, the present invention provides a uniformly coated lithium cobalt oxide positive electrode material, which has the advantages of high capacity, good cycle stability, and can be matched with solid-state batteries. In addition, the synthesis process is simple, the production efficiency is high, the product uniformity is good, and it is suitable for large-scale production.

[0006] The specific technical solutions of the present invention are as follows:

[0007] A method for preparing a modified lithium cobalt oxide positive electrode material comprises the following steps:

[0008] (1) mixing cobalt trioxide and lithium salt in a molar ratio of Co in cobalt trioxide to Li in lithium salt of 1:1.05 to obtain a mixture;

[0009] (2) placing the mixture in an air atmosphere and subjecting it to a first calcination to obtain a lithium cobalt oxide positive electrode material;

[0010] (3) mixing the lithium cobalt oxide positive electrode material and aluminum triethoxide in a molar ratio of Co in the lithium cobalt oxide positive electrode material: Al in aluminum triethoxide of 1: (γ×δ), and performing a second calcination to obtain lithium cobalt oxide coated with aluminum oxide, wherein 0<γ≤0.1, 0<δ≤0.5;

[0011] (4) The alumina-coated lithium cobalt oxide is uniformly mixed with a lithium source, a titanium source and a phosphorus source according to a molar ratio of Al in the alumina-coated lithium cobalt oxide: Li in the lithium source: Ti in the titanium source: P in the phosphorus source of δ: (1+δ): (2-δ): 3, and then calcined for the third time. After the third calcination, most of the alumina coating layer obtained in step (3) is converted into a LATP layer, but a small part is still coated on the outer layer of the lithium cobalt oxide, so that a "double-coated" modified lithium cobalt oxide positive electrode material can be obtained.

[0012] Furthermore, the lithium salt in step (1) is lithium carbonate.

[0013] Furthermore, in step (4), the lithium source is lithium hydroxide, the titanium source is tetraisopropoxytitanium, and the phosphorus source is diammonium phosphate.

[0014] Furthermore, the calcination temperature of the first calcination is 800~1100℃, and the calcination time is 5~24h; the calcination temperature of the second calcination is 300~500℃, and the calcination time is 0.5~2h; the calcination temperature of the third calcination is 300~800℃, and the calcination time is 1~5h.

[0015] The present invention also discloses a modified lithium cobalt oxide positive electrode material, the molecular formula of which is:

[0016] LiCoO2@γLi 1+δ Al δ Ti 2-δ (PO4)3,

[0017] Among them, Li 1+δ Al δ Ti 2-δ (PO4)3 is the general molecular formula of the coating material, 0<γ≤0.1, 0<δ≤0.5.

[0018] Furthermore, the modified lithium cobalt oxide positive electrode material is prepared by any of the above-mentioned preparation methods.

[0019] The present invention also discloses the application of any of the above-mentioned modified lithium cobalt oxide positive electrode materials in the field of battery materials.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] When preparing the modified lithium cobalt oxide positive electrode material, the present invention can dope a small amount of aluminum into the lithium cobalt oxide positive electrode material by mixing the lithium cobalt oxide positive electrode material with triethanol aluminum and then calcining it, and can simultaneously coat the surface of the lithium cobalt oxide positive electrode material with an aluminum oxide layer, which can effectively inhibit the interface side reaction. In the subsequent coating process, most of the aluminum oxide layer will be converted into an LATP layer, and a small amount of aluminum oxide phase will still exist inside, so a "double-coated" stable structure can be formed. At the same time, since the present invention uses triethanol aluminum as the aluminum source, no impurities will be generated during the coating process. Therefore, the modified lithium cobalt oxide positive electrode material prepared by the present invention has stable physical and chemical properties, good crystallinity and layered structure, and excellent battery cycle performance. After 200 cycles, the capacity retention rate of the lithium cobalt oxide positive electrode material of the present invention can reach 85.9~92.5%.

[0022] Compared with the traditional coating method, the method of the present invention has the advantages of simple synthesis process, high production efficiency, good product uniformity, and suitable for large-scale production. In addition, the method of the present invention has the advantages of easy availability of reaction raw materials, low cost, no need for special protection during the production process, easy control of reaction conditions, large yield of the obtained product, good result reproducibility, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD pattern of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention;

[0024] Figure 2 This is the XRD pattern of the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1;

[0025] Figure 3 This is a comparison chart of the discharge specific capacity cycle of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention and the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 under the conditions of 2C (400 mA / g) and 4.6V cut-off voltage;

[0026] Figure 4 The charge and discharge curves of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention and the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 under the conditions of 0.1C (20 mA / g) and 4.6V cut-off voltage. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.

[0028] Unless otherwise specified, the reagents, equipment and materials described in the following examples and comparative examples can be obtained from commercial sources.

[0029] The test methods for various properties of the modified lithium cobalt oxide positive electrode materials prepared in the examples and comparative examples are as follows:

[0030] X-ray diffraction technology (XRD): The detection instrument is Dandong Haoyuan's XRD instrument, model DX-2700BH. The radiation source is Cu Kα, the tube voltage is set to 40kV, and the tube current is set to 30mA. During the scanning process, the scanning rate is controlled at 2° / min to ensure the accuracy of the data. The scanning range of the 2θ angle is 10° to 80° to cover a wider range of material structure information.

[0031] Lithium ion battery cycle performance test: The lithium cobalt oxide positive electrode material prepared in the embodiment and the comparative example is made into a positive electrode sheet, and assembled into a lithium ion battery with a negative electrode sheet, a diaphragm and an electrolyte, and then the discharge specific capacity cycle and average voltage under 2C (400mA / g) and 4.6V cut-off voltage conditions are tested. The specific steps are: prepare the lithium cobalt oxide positive electrode material, SP and PVDF according to the mass ratio of 8:1:1, mix them with NMP, place them on a magnetic stirrer and stir them until uniform, apply the prepared slurry into a pole sheet, transfer it to a vacuum drying oven, and vacuum dry it at 120°C for 12h. The pole sheet is cut into 12mm discs for battery assembly. In the glove box, the positive electrode shell, positive electrode sheet, diaphragm, lithium sheet and negative electrode shell are assembled in order, and the electrolyte is LiPF6 electrolyte, and a lithium ion battery is obtained after assembly. The present invention uses the Landian LANHECT2001A charge and discharge instrument of Wuhan Rambo Electronics Co., Ltd. to perform constant current charge and discharge and cycle performance tests on it.

[0032] Example 1

[0033] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0034] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0035] (2) Sintering: calcining the mixture at 1000°C for 14 hours in an air atmosphere to obtain a lithium cobalt oxide positive electrode material;

[0036] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide to Al in triethoxide aluminum of 1: (0.02×0.3). The evenly mixed mixture is then calcined at 300°C for 2 hours to obtain lithium cobalt oxide coated with alumina;

[0037] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), ammonium dihydrogen phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al in lithium hydroxide: Li in lithium hydroxide: Ti in tetraisopropoxytitanium: P in ammonium dihydrogen phosphate) were mixed uniformly according to the molar ratio of 0.3: (1 + 0.3): (2-0.3): 3, and then calcined at 700 ° C for 1 hour to obtain the target product (LiCoO2@0.02Li 1.3 Al 0.3 Ti 1.7 (PO4)3).

[0038] Embodiment 2:

[0039] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0040] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0041] (2) Sintering: calcining the mixture at 900°C in an air atmosphere for 24 hours to obtain a lithium cobalt oxide positive electrode material;

[0042] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide to Al in triethoxide aluminum of 1:(0.1×0.5). The evenly mixed mixture is then calcined at 500°C for 0.5 hours to obtain lithium cobalt oxide coated with aluminum oxide;

[0043] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al) : Li in lithium hydroxide (Li) : Ti in tetraisopropoxytitanium (Ti) : P in diammonium phosphate (NH4H2PO4) are mixed evenly according to the molar ratio of 0.5: (1+0.5) : (2-0.5) : 3, and then calcined at 400°C for 4 hours to obtain the target product.

[0044] Embodiment 3:

[0045] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0046] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0047] (2) Sintering: calcining the mixture at 800°C in an air atmosphere for 24 hours to obtain a lithium cobalt oxide positive electrode material;

[0048] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide to Al in triethoxide aluminum of 1:(0.04×0.1). The evenly mixed mixture is then calcined at 400°C for 1 hour to obtain lithium cobalt oxide coated with alumina;

[0049] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al) : Li in lithium hydroxide (Li) : Ti in tetraisopropoxytitanium (Ti) : P in diammonium phosphate (NH4H2PO4) are mixed evenly according to the molar ratio of 0.1: (1+0.1) : (2-0.1) : 3, and then calcined at 800°C for 1 hour to obtain the target product.

[0050] Embodiment 4:

[0051] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0052] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0053] (2) Sintering: calcining the mixture at 900°C in an air atmosphere for 24 hours to obtain a lithium cobalt oxide positive electrode material;

[0054] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide to Al in triethoxide aluminum of 1:(0.08×0.1). The evenly mixed mixture is then calcined at 300°C for 1 hour to obtain lithium cobalt oxide coated with alumina;

[0055] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al) : Li in lithium hydroxide (Li) : Ti in tetraisopropoxytitanium (Ti) : P in diammonium phosphate (NH4H2PO4) are mixed evenly according to the molar ratio of 0.1: (1+0.1) : (2-0.1) : 3, and then calcined at 700°C for 1.5 hours to obtain the target product.

[0056] Embodiment 5:

[0057] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0058] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0059] (2) Sintering: calcining the mixture at 1100°C in an air atmosphere for 5 hours to obtain a lithium cobalt oxide positive electrode material;

[0060] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide to Al in triethoxide aluminum of 1:(0.1×0.5). The evenly mixed mixture is then calcined at 350°C for 1 hour to obtain lithium cobalt oxide coated with alumina;

[0061] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al) : Li in lithium hydroxide (Li) : Ti in tetraisopropoxytitanium (Ti) : P in diammonium phosphate (NH4H2PO4) are mixed evenly according to the molar ratio of 0.5: (1+0.5) : (2-0.5) : 3, and then calcined at 500°C for 2 hours to obtain the target product.

[0062] Embodiment 6:

[0063] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0064] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0065] (2) Sintering: calcining the mixture at 1050°C for 12 hours in an air atmosphere to obtain a lithium cobalt oxide positive electrode material;

[0066] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide: Al in triethoxide aluminum of 1:(0.03×0.4). The evenly mixed mixture is then calcined at 450°C for 1 hour to obtain lithium cobalt oxide coated with alumina;

[0067] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al) : Li in lithium hydroxide: Ti in tetraisopropoxytitanium: P in diammonium phosphate are mixed uniformly according to the molar ratio of 0.4: (1+0.4) : (2-0.4) : 3, and then calcined at 600°C for 4 hours to obtain the target product.

[0068] Embodiment 7:

[0069] This embodiment discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0070] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0071] (2) Sintering: calcining the mixture at 1100° C. for 12 hours in an air atmosphere to obtain a lithium cobalt oxide positive electrode material;

[0072] (3) The sintered lithium cobalt oxide positive electrode material and triethoxide aluminum ((C2H5O)3Al) are mixed evenly according to the molar ratio of Co in lithium cobalt oxide: Al in triethoxide aluminum of 1:(0.03×0.35). The evenly mixed mixture is then calcined at 450°C for 1.5 hours to obtain lithium cobalt oxide coated with alumina;

[0073] (4) The above-mentioned alumina-coated lithium cobalt oxide is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), diammonium phosphate (NH4H2PO4) and alumina-coated lithium cobalt oxide (Al in lithium hydroxide: Li in lithium hydroxide: Ti in tetraisopropoxytitanium: P in diammonium phosphate are mixed uniformly according to the molar ratio of 0.35: (1 + 0.35): (2-0.35): 3, and then calcined at 300 ° C for 5 hours to obtain the target product.

[0074] Comparative Example 1

[0075] This comparative example discloses a method for preparing a lithium cobalt oxide positive electrode material, comprising the following steps:

[0076] (1) Cobalt tetroxide and lithium carbonate are uniformly mixed according to a molar ratio of Co in cobalt tetroxide to Li in lithium carbonate of 1:(1.05×1);

[0077] (2) Sintering: The mixture is calcined at 1000°C in an air atmosphere for 14 hours to obtain a lithium cobalt oxide positive electrode material.

[0078] Comparative Example 2

[0079] This comparative example discloses a method for preparing a modified lithium cobalt oxide positive electrode material, comprising the following steps:

[0080] (1) Same as step (1) in Example 1;

[0081] (2) Same as step (2) in Example 1;

[0082] (3) Aluminum triethanolate ((C2H5O)3Al) was mixed with 15 ml of ethanol, and the sintered lithium cobalt oxide positive electrode material was added thereto with stirring. After ultrasonic treatment for half an hour, the mixture was placed on a magnetic stirrer and the heating temperature was set to 70°C and the stirring rate was set to 350 r / min. The above solution was evaporated to dryness and then dried in an oven at 80°C for 12 hours to obtain a lithium cobalt oxide positive electrode material coated with aluminum triethanolate, wherein the molar ratio of Co in the lithium cobalt oxide positive electrode material: Al in aluminum triethanolate was 1: (0.02×0.3).

[0083] (4) The lithium cobalt oxide obtained in step (3) is mixed with lithium hydroxide (LiOH) and tetraisopropoxytitanium (C 12 H 28 O4Ti), ammonium dihydrogen phosphate (NH4H2PO4) and triethylaluminum-coated lithium cobalt oxide (Al in lithium hydroxide): Li in tetraisopropoxytitanium: Ti in ammonium dihydrogen phosphate (P) were mixed evenly according to the molar ratio of 0.3: (1 + 0.3): (2-0.3): 3, and then calcined at 700 ° C for 1 hour to obtain the target product (LiCoO2@0.02Li 1.3 Al 0.3 Ti 1.7 (PO4)3).

[0084] Comparative Example 3

[0085] The difference between this comparative example and Example 1 is that in step (3), the triethanol aluminum in Example 1 is replaced by Al(NO3)3·9H2O, and the rest is exactly the same as Example 1.

[0086] Performance test results:

[0087] Figure 1 This is the XRD pattern of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention. Figure 2 The XRD pattern of the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 is shown in FIG. Figure 1 It can be obtained that no impurity peaks are generated in the XRD of Example 1 and Comparative Example 1. The modified lithium cobalt oxide positive electrode material in Example 1 has a higher XRD diffraction peak intensity than the unmodified lithium cobalt oxide positive electrode material in Comparative Example 1, indicating that the coated modified lithium cobalt oxide positive electrode material has better crystallinity and layered structure.

[0088] Figure 3 This is a comparison chart of the discharge specific capacity cycles of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention and the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 under the conditions of 2C (400 mA / g) and 4.6V cut-off voltage. Figure 4 The charge and discharge curves of the coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention and the unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 under the conditions of 0.1C (20 mA / g) and 4.6V cut-off voltage. Figure 3 , Figure 4 It can be seen that the coated lithium cobalt oxide positive electrode material prepared by the method of the present invention has obvious improvement effects in improving capacity, improving capacity attenuation and inhibiting structural degradation compared with the unmodified lithium cobalt oxide positive electrode material.

[0089] At 25°C, the cycle performance of each lithium cobalt oxide button cell at 2C rate was tested, and the capacity retention rate after 200 cycles was calculated. The test results are shown in Table 1:

[0090] Table 1

[0091]

[0092] From Table 1, we can get:

[0093] The positive electrode materials prepared by using Examples 1 to 7 of the present invention have excellent cycle stability. After 200 cycles, the capacity retention rate can be maintained in an excellent range of 85.9% to 92.5%.

[0094] Compared with Example 2, Example 1 does a certain amount of element Al on the surface of the positive electrode material in Example 2, which can effectively stabilize the layered structure and prevent phase change to a certain extent. Compared with the unmodified lithium cobalt oxide positive electrode material (Comparative Example 1), the cycle stability is improved to a certain extent. After 200 cycles, the capacity retention rate is increased by 5.3% (see Table 1). However, this method still has the following defects: the surface doped element Al will react with LiPF6 in the electrolyte during the cycle, resulting in instability at the interface between the positive electrode and the electrolyte and loss of Al elements in the bulk phase. However, Example 1 coats the metal oxide Al2O3 on Al-doped LiCoO2, effectively inhibiting the interfacial side reactions and significantly improving the cycle performance of the battery. The capacity retention rate is still 92.5% after 200 cycles.

[0095] Compared with Example 3, the aluminum source used in Example 1 greatly improves the electrochemical properties of the coating layer, not only does not affect the crystallinity of the lithium cobalt oxide material, but also has high ionic conductivity, thereby improving the overall cycle stability. In Comparative Example 3, a water-soluble aluminum nitrate is used. Under the same conditions, the aluminum source is not fully mixed with other raw materials to form AlPO4 impurities, which have poor stability to lithium ions, and its internal crystal structure is affected by factors such as battery polarization and electrolyte degradation. The assembled battery has a short test life, and the capacity retention rate after 200 cycles is reduced by 16.7% compared with Example 1.

Claims

1. A method for preparing a modified lithium cobalt oxide positive electrode material, characterized in that: The steps include: (1) mixing cobalt trioxide and lithium salt in a molar ratio of Co in cobalt trioxide to Li in lithium salt of 1:1.05 to obtain a mixture; (2) placing the mixture in an air atmosphere and subjecting it to a first calcination to obtain a lithium cobalt oxide positive electrode material; (3) mixing the lithium cobalt oxide positive electrode material and aluminum triethoxide in a molar ratio of Co in the lithium cobalt oxide positive electrode material: Al in aluminum triethoxide of 1: (γ×δ), and performing a second calcination to obtain lithium cobalt oxide coated with aluminum oxide, wherein 0<γ≤0.1, 0<δ≤0.5; (4) The alumina-coated lithium cobalt oxide is uniformly mixed with a lithium source, a titanium source and a phosphorus source according to a molar ratio of Al in the alumina-coated lithium cobalt oxide: Li in the lithium source: Ti in the titanium source: P in the phosphorus source of δ: (1+δ): (2-δ): 3, and then calcined for a third time to obtain a modified lithium cobalt oxide positive electrode material.

2. The method for preparing the modified lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The lithium salt in step (1) is lithium carbonate.

3. The method for preparing the modified lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In step (4), the lithium source is lithium hydroxide, the titanium source is tetraisopropoxytitanium, and the phosphorus source is diammonium phosphate.

4. The method for preparing the modified lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The calcination temperature of the first calcination is 800~1100℃, and the calcination time is 5~24h; The calcination temperature of the second calcination is 300~500℃, and the calcination time is 0.5~2h; The calcination temperature of the third calcination is 300~800℃, and the calcination time is 1~5h.

5. A modified lithium cobalt oxide positive electrode material, characterized in that: The molecular formula is: LiCoO2@γLi 1+δ Al δ Ti 2-δ (PO4)3, among which Li 1+δ Al δ Ti 2-δ (PO4)3 is the molecular formula of the coating material, 0<γ≤0.1, 0<δ≤0.5; The modified lithium cobalt oxide positive electrode material is prepared by the preparation method of the modified lithium cobalt oxide positive electrode material according to any one of claims 1 to 4.

6. Application of the modified lithium cobalt oxide positive electrode material according to claim 5 in the field of battery materials.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material with aluminum-doped surface and titanium-aluminum-lithium phosphate-coated surface and preparation thereof

    CN111987297A

  • Li1+xAlxTi2-x (PO3)4-coated lithium cobalt oxide material and preparation method and application thereof

    CN109994722A